Effect of pre-germination treatments in Dianthus barbatus L. seeds cv. 'Purple' under controlled conditions - González-Amaya, Leidy Julieth; Pita, Bayron Eduardo; Pinzón-Sandoval, Elberth Hernando; Cely, German Eduardo; Serrano, Pablo Antonio (Revista de Ciencias Agrícolas, 2018)
Carnations are the most desired flowers because their excellent characteristics of endurance and beauty. However, the species Dianthus barbatus L. cv. 'Purple', face problems in the germination stage, which leads to increased production costs. Therefore, the objective of the research was to test different pre-germination treatments on the seed germination of Dianthus barbatus L. cv 'Purple'. A Completely Randomized Design was established with ten treatments corresponding to the combination of three doses of KNO3 (150, 200, 250 mg L-1) and three imbibition periods (6, 12, 24 hours) including the control treatment. The evaluated variables were: percentage of germination (PG), water absorbed, germination speed average (ASG), germination time average (ATG), percentage of adaptability (PA). The application of pre-germination treatments based on the application of KNO3 combined with the imbibition showed a positive effect on the percentage of, ASG, ATG, imbibition rate and adaptation in seeds of Dianthus barbatus L. cv. 'Purple' under controlled conditions. The treatment that generated the best response was the application of KNO3 at a concentration of 250 mg L-1 and six hours of imbibition, which presented significant differences (P≤0.05) compared to the control treatment in most of the evaluated variables. It becomes an important alternative in the reduction of production costs within the process of sexual propagation of D. barbatus L. cv 'Purple' under controlled conditions.